Validação psicométrica dos bancos de itens de ansiedade e depressão do patient-reported outcomes measurement information system – PROMIS® (versão 1.0) para a população brasileira - Castro, Natália Fontes Caputo de (2018)
Introduction: Scientific evidence indicates that the symptoms of anxiety and depression can be understood as risk factors associated with the incidence and progression of chronic diseases, in addition to having a negative impact on the quality of life related to patients’ health. The Emotional Distress Items (Anxiety and Depression Banks) of the Patient-Reported Outcomes Information System (PROMIS®) (Version 1.0) developed by US researchers represent a methodological improvement of Patient-Reported Outcomes (PRO). The Banks allow a more reliable evaluation of the psychological constructs, provide complementary information that helps in the clinical diagnosis and allow a flexible application, collaborating for its effective implementation in the clinical and epidemiological contexts. Objective: to validate the psychometric properties of the Emotional Distress items (Anxiety and Depression Bank) for the Brazilian population. Methods: 606 adults responded self-administered items of Anxiety and Depression that were calibrated through the Exploratory and Confirmatory Factorial Analysis and adjustment of the Graded Response Model (GRM), in which the cross-cultural validity was evaluated by the Differential Item Functioning of the Item (DIF). Results: The bifactorial analysis confirmed the unidimensionality (CFI = 0.96, TLI = 0.96, RMSEA = 0.05) of the Emotional Distress items, and the residual correlation matrix did not identify pairs of items with local dependence. The calibration process evidenced discrimination parameters greater than 1.0 for all items, while the indicators marked with DIF presented an impact of low magnitude for the variables of gender, age and language. The instrument demonstrated greater reliability in the region that corresponds to the moderate to severe range, which shows that the reduction of the measurement error reflected on the amplitude of -1.0 and +3.0. Conclusions: There was equivalence between the psychometric measures of the Brazilian version of PROMIS® Emotional Distress Items (Anxiety and Depression Item Banks) and the original version. Additional research involving patients with different levels of emotional distress will be necessary to better infer the results of this study.